Application of Change Strategy to Business in the Covid-19 Pandemic Period (Case Study on MSME Bakor Medan) - Niki Aulia; Nuri Aslami (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
This research was attempted to identify the business strategy applied by Micro, Small and Medium Enterprises (MSMEs) actors in experiencing the COVID-19 pandemic in one of the area's city zones. The research subject is an effort to eat with the Bakor Area business brand which is located on Jln. Tempuling City Area. The procedure used is a qualitative research procedure with a descriptive approach. From the results of the research, it is known that MSMEs named Bakor Area know that the exploitation of the internet and social tools as a sales tool and assisted by good quality products and services as a business strategy that is right for application, especially in the midst of the COVID-19 endemic, can not only maintain sustainability Efforts can also increase the network and create a good view of the customers, thereby encouraging the development of the business sector